Penilaian Kinerja Individu Pegawai Pemerintah Kota Malang - Pio, Riane Johnly (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstracts. This study aims to determine the employee's perception of the assessment of individual performance based on indicators developed from the list of assessment implementation work. The method used is descriptive qualitative judgment sampling with sampling which is representative of the leadership and staff of the Regional Employment Board of Malang. The results show the model is fairly good assessment to assess the performance of public servants since been standardized and easy for top decision makers in the field of national personnel to evaluate and make policy. However, each type of job has a different assessment dimensions, so that a good assessment should be based on factual work of each individual. Especially in the era of autonomous forms of assessment using the DP3 is irrelevant because the system of government has changed. It seems unfair if the employee performance appraisal conducted uniformly throughout Indonesia. All you need do is to integrate the existing appraisal system for civil servants with other relevant assessment system and accommodate the situation and condition of the local government. Â Keywords: Performance Assessment, Individual Employee